Pemberantasan Buta Aksara untuk Peningkatan Kualitas Sumber Daya Manusia Masyarakat Sekitar Hutan Desa Manipi, Kecamatan Pana, Kabupaten Mamasa - Vega Jessica; Ardian Halis; Dwi Wahyu Ningsi; Ghita Firsty Virginia; . Syahidah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Illiteracy is one of the basic issue that hinder the quality of human resources. In order to improve the quality of human resources, one of the fundamental things that must be fulfilled is eradicate illiteracy of community. The aim of this study are to enhance literacy of the forest community in Manipi Village, Pana Sub-District, Mamasa District, West Sulawesi. Manipi Village have abundant natural resources, such as wood and non-wood forest product. On the other hand, this area also relatively isolated due to it is difficult accessibility. Therefore, the resident also unable to access education so that illiteracy rate is quite high. Illiteracy eradicating were arrange in cooperation with PKBM Harapan Bersama, and NGO that focused in illiteracy eradicating. Literacy of resident before and after this program were measured by a pre test and a post test. The age of the partisipant were 17–59 years with total 55 partisipants. The program divided into three steps, namely reading, writing, and counting steps. Every step refers to the teaching module and conducted with the attractive way. The result showed that literacy of partisipant increased from 11 to 70%, writing increased from 9 to 70%, while for the counting increased from 15 to 71%.